Estudio de la expresión de la 11 beta-hidroxiesteroide deshidrogenasa-1 (11 beta-HSD1) y del péptido símil glucagón-1 (GLP-1) en perros con síndrome de Cushing - Miceli, Diego Daniel (2017)
Cushing's syndrome (CS) is defined as chronic glucocorticoid excess in blood. It is one of the most prevalent endocrine-diseases in dogs. The CS is characterized by\ndisturbances in the metabolism of carbohydrates and lipids, among which highlights\nthe trend of fasting hyperglycemia, hypercholesterolemia, hypertriglyceridemia,\nhepatic steatosis and, in severe cases, Diabetes Mellitus (DM). These disturbances\narise because cortisol antagonizes many insulin´s functions, inducing a state of\ninsulin resistance.\nGlucagon like peptide 1 (GLP-1) is an intestinal peptide which enhances insulin secretion. The levels of GLP-1 are reduced in humans with DM. The 11?\nHydroxysteroid Dehydrogenase type 1 (11?-HSD1) is an enzyme that converts cortisone to cortisol in tissues and its alteration is related to the development of Metabolic Syndrome, Obesity and CS. The endothelial Nitric Oxide Synthase (eNOS)\nproduces nitric oxide (NO) and is involved in the fine regulation of adrenal\nsteroidogenesis. Metformin is a drug widely used in the treatment of human DM\nreducing hyperglycemia, dyslipidemia and insulin resistance. The aims of this thesis were to assess whether there are changes in the expression\nof 11?-HSD1 and eNOS and the concentration of GLP-1 in dogs with CS, compared\nto healthy dogs. In turn, assess whether these changes are related to the persistence of hypercortisolism, dyslipidemia and progression to DM in dogs with CS. Study the\nconcurrence between CS and DM and assess potential risk factors in dogs with CS that could predispose the development of DM concurrently. Also, valuate if metformin\namends such metabolic disorders. Estudio de la 11?-HSD1 y del GLP-1 en perros con Síndrome de Cushing\nOral Glucose Tolerance Test (OGTT) in dogs with CS, obeses and controls dogs\nwere performed, and levels of GLP-1, insulin and glucose levels at times 0, 15, 30, 60 and 120 minutes were evaluated. In parallel, the Homeostatis Model Assessment (HOMA) was evaluated as well as levels of GLP-1 in dogs with CS and DM, and dogs\nwith DM. In turn, visceral adipose tissue samples of dogs with CS were taken and enzymatic expression of 11?-HSD1 by immunohistochemistry and western blot was evaluated. Also, adrenal glands samples of dogs with CS were taken and enzyme\neNOS expression was assessed by immunohistochemistry. Levels of plasmatic NO\nwere also evaluated. Concurrence between CS and DM was studied, survival was calculated and risk factors were evaluated in dogs with CS that could predispose the\ndevelopment of DM. Finally, adjunctive therapy with metformin in dogs with CS was implemented to assess whether metabolic abnormalities are corrected.\nCS dogs had higher levels of GLP-1 (p<0.01), glucose (p<0.01) and insulin (p<0.01),\nlower insulin sensitivity (p<0.01) and higher functionality of pancreatic ? cell (p<0.01). Obese presented an intermediate behavior. The highest concentrations of GLP-1\ncould overstimulate pancreatic ? cell, predisposing depletion and subsequent development of DM. DM affected dogs had similar levels of GLP-1 to those dogs with\nCS. The expression of the enzyme 11?-HSD1 in adipocytes of visceral adipose tissue of dogs with CS was significantly higher compared to controls dogs (p<0.01). The enzyme eNOS expression in the adrenal cortex (fasciculata) of dogs with CS was significantly lower compared to controls and obese dogs (p<0.05, p<0.001). Plasma NO levels were significantly lower in dogs with CS compared to control dogs (p<0.001). The concurrence of CS and DM is 13.61%. Dogs with blood glucose Estudio de la 11?-HSD1 y del GLP-1 en perros con Síndrome de Cushing\nlevels > 100 mg/dl (p<0.01, RR 1.16, PPV 0.98), total cholesterol > 350 mg/dL\n(p<0.01, RR 1.13, PPV 0.98), triglycerides > 250 mg/dl (p<0.05, RR 1.17, PPV 0.95), with cortisol urine creatinine ratio > 100x10-6 (p<0.05, RR 1.13, PPV 0.95) are at increased risk of developing DM. Dogs with pituitary adenoma (p<0.05, RR 0.85, PPV 0.08) and not spayed females (p<0.05, RR 0.86, PPV 0.77) are more prone to develop DM. The appearance of DM in dogs with CS reduces survival time (p<0.01\nHazard ratio: 0.36). Early detection of risk factors will allow to implement therapies to reduce the incidence of DM in dogs with CS. Introducing metformin therapy was effective in normalizing blood glucose (p<0.01), triglycerides (p<0.05) and total\ncholesterol (p<0.01) during the first months of treatment and shorten recovery times.\nKey words: Cushing´s syndrome, glucagon like peptide-1, 11?-Hydroxysteroid\nDehydrogenase type 1, endothelial Nitric Oxide Synthase, Metformin, Diabetes Mellitus.